SOSIALISASI 3R (REDUCE, REUSE, RECYCLE) KEPADA IBU-IBU PKK DI DESA SOKOYOSO, KEC.KAJEN, KAB.PEKALONGAN OLEH MAHASISWA KKN UNIVERSITAS PEKALONGAN - Kafilatul Khoiriyah; Bertha Indi Iranela; Bunga Azimatul Aulia; Adilatul Lishowabah; Fadia Rahma Putri; Anisa Putri Rahayu; Yayan Melinda; Ecytha Rachel Permana; Widya Dewi Valentina; Ahmad Fakhri Annabil; Tegar Wida Rahma; Khafid Mahbub; Herlambang Fitnanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This community service focuses on addressing the lack of public awareness regarding domestic waste management in Sokoyoso Village, Kajen District, Pekalongan Regency. The conventional habits of burying and burning waste openly still dominate, posing risks to health and environmental sustainability. To address this issue, a KKN program conducted an intensive socialization campaign focusing on the 3R (Reduce, Reuse, Recycle) concept. The method employed was an interactive educational seminar combined with the distribution of informative leaflets to village residents. The result of this activity showed a significant 65% increase in community knowledge regarding correct waste classification and the urgency of eco-friendly waste management. In conclusion, this theoretical socialization effectively builds foundational community environmental awareness, establishing a critical stepping stone for future village-scale waste management initiatives.